Penggunaan Pendekatan Sistem-S dan ESSYNS dalam Analisis Taburan Normal - Lee, Muhammad Hisyam (Universiti Putra Malaysia Press, 1994)
The purpose of this paper is to illustrate the use of S-systems methodology and ESSYNS software in the area of computational statistics. First, we demonstrate how the densities are formulated as S-systems, then we derive representations for cumulatives and quantiles. Cumulatives are obtained with little extra effort and quantiles are readily calculated from the inverted S-system. These representations are then solved numerically using ESSYNS. The density and the cumulative curves for the normal distribution are generated for the values in the range (-3,3). The S-system method produces many quantiles in a single computer run. The use of S-system generalizations and approximation has shown to be a useful alternative method for analysing distributions.